Independence of The General Election Commission In Carrying Out Factual Verification of Political Parties General Election Participants - Azis, Imron Rizki; La Dee, Mustakim; Salam, Safrin; Kaswandi, Kaswandi (Universitas Muhammadiyah Surabaya, 2023)
Political parties are an important aspect that determines the quality of holding good general elections, because political parties are the first door for candidates for government administration. Find out what are the requirements for political parties to become participants in the General Election (PEMILU) and how to carry out factual verification of political parties. The statutory and analytical approach through literature studies related to the factual verification of political parties participating in general elections. There are parties that were previously declared ineligible, then later after taking legal or administrative measures they were passed, meaning that there was implementation that was not optimal or error in the field.